Sulfur-vacancy-rich ZnIn2S4-coated AgBiS2 heterojunction photocatalytic composite material as well as preparation method and application thereof
By combining sea urchin-like AgBiS2 with sulfur vacant ZnIn2S4 nanosheets to form an S-type heterojunction composite material, the problem of limited applications of ZnIn2S4 carrier composite and AgBiS2 is solved, and efficient photocatalytic hydrogen production and organic pollutant degradation is achieved.
Patent Information
- Application Number
- CN202411558994.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-14
AI Technical Summary
ZnIn2S4 has carrier recombination and wide band gap problems when photocatalyzed decomposition of water to produce hydrogen, which affects its absorption of sunlight; the application of AgBiS2 in the field of photocatalysis is limited by its two-dimensional film structure and substrate shading. question.
A sea urchin-shaped AgBiS2 semiconductor material and ZnIn2S4 nanosheets with sulfur vacancy were used to form an S-type heterojunction composite material. ZnIn2S4 nanosheets were grown in situ by a low-temperature one-step oil bath method to form a cauliflower-shaped sulfur-rich vacancies ZnIn2S4@AgBiS2 heterojunction Catalytic composites.
The photocatalytic hydrogen production efficiency is improved, the degradation efficiency of tetracycline hydrochloride and rhodamine B is improved, and extremely stable and high reusable rate is shown.
Smart Images

Figure CN119425730A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic materials, and in particular to a sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material, and a preparation method and application thereof. Background Art
[0002] The use of solar energy to photocatalytically decompose water to produce hydrogen and degrade pollutants has a good development prospect in the field of energy and environment. In order to effectively utilize sunlight, ZnIn2S4, as a typical transition metal sulfide, has the characteristics of simple and diverse synthesis methods and controllable morphology, but serious carrier recombination and wide band gap affecting its absorption of sunlight have restricted the further improvement of its photocatalytic activity.
[0003] Vacancy defect engineering can be used to solve the above problems. However, a single photocatalytic material cannot meet all the conditions required for photocatalytic reactions. In addition, modification strategies such as heterojunction construction are considered to be a means to improve the photocatalytic performance of semiconductor materials. Among the many types of heterojunctions, S-type heterojunctions have been widely reported due to their unique electron transfer mechanism and low carrier recombination. The key to constructing S-type heterojunctions is to select semiconductor materials with suitable band edge positions. At present, most people use metal oxides with strong oxidizing properties in the valence band position to construct heterojunctions. Among them, TiO2 with a suitable band structure can form a band arrangement that is conducive to the separation of photogenerated electrons and holes when constructing heterojunctions with other semiconductor materials, and has been widely studied. However, metal oxides have limited light absorption range due to their large bandgap width, and there are problems such as serious photogenerated carrier recombination, which limits their further development. AgBiS2 is a ternary transition metal sulfide with high optoelectronic performance. It is usually widely used in thin-film solar cells and ion batteries in the form of two-dimensional thin-film large grains grown on substrates, but it is rarely reported in the field of photocatalysis. Since only one side of the AgBiS2 film on the substrate is in contact with water, and the other side is blocked by the substrate, if it is directly applied in the field of photocatalysis, not only will the area of the photocatalytic reaction be greatly reduced, but the light absorption of AgBiS2 will also be weakened due to the shielding of light by the substrate. In addition, the heterojunction formed by epitaxy has high requirements on the crystal quality and surface flatness of the AgBiS2 film, so even if AgBiS2 is applied in the field of photocatalysis, it is greatly limited and cannot be widely used. Summary of the invention
[0004] In order to solve the problems of severe carrier recombination and wide band gap affecting the absorption of sunlight when ZnIn2S4 is used for photocatalytic decomposition and hydrogen production, and the problem of limited application of AgBiS2 in the field of photocatalysis, the present invention provides a sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material, and also provides a preparation method and application thereof.
[0005] The first purpose of the present invention is to provide a sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material, which is an S-type heterojunction composite material formed by growing ZnIn2S4 nanosheets containing sulfur vacancies (as embodied in claim 1) on a sea urchin-shaped AgBiS2 semiconductor material. When the ZnIn2S4 nanosheets grow on the sea urchin-shaped AgBiS2, they exhibit a cauliflower-like morphology.
[0006] In the present invention, a sea urchin-shaped AgBiS2 semiconductor material is used, which is a three-dimensional structure and has a larger specific surface area than the current two-dimensional thin film AgBiS2. More importantly, the sea urchin-shaped three-dimensional AgBiS2 can form an S-type heterojunction with a ZnIn2S4 nanosheet with sulfur vacancies, has light absorption ability, can regulate and control the electronic energy band structure, accelerate charge transfer, and the internal sulfur vacancies can act as electron capture centers to inhibit the recombination of photogenerated electron-hole pairs. Under the dual synergistic catalytic action of sulfur vacancies and S-type heterojunctions, the composite material exhibits excellent photocatalytic hydrogen production and degradation of tetracycline hydrochloride and rhodamine B. At the same time, in the present invention, the morphology and size of ZnIn2S4 before and after the composite are greatly changed, forming a cauliflower-shaped sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material. The cauliflower-shaped ZnIn2S4 has a smaller size, which leads to a larger specific surface area, and the area of contact with water and the photocatalytic reaction is also larger, which is more conducive to the reaction.
[0007] In the present invention, a cauliflower-shaped sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material is obtained by in-situ growth of ZnIn2S4 nanosheets on a sea urchin-shaped AgBiS2 semiconductor material. The internal sulfur vacancies can act as electron capture centers to inhibit the recombination of photogenerated electron-hole pairs. It exhibits extremely strong stability under multiple photocatalytic cyclic hydrogen production and tetracycline hydrochloride degradation tests, is easy to recycle, has a high reusability, and has good commercial value.
[0008] In an optional embodiment, the ZnIn2S4 nanosheets containing sulfur vacancies have a thickness of 15 to 25 nm and a size of 500 to 800 nm. When the ZnIn2S4 nanosheets grow on the sea urchin-shaped AgBiS2, they exhibit a cauliflower-like morphology, forming nanosheets with a thickness of 15 to 25 nm and a size of 50 to 100 nm, and the morphology and size have changed significantly.
[0009] In an optional embodiment, the sea urchin-shaped AgBiS2 semiconductor material is micron-sized and has a cubic crystal structure.
[0010] In the present invention, by regulating the morphology, size and crystal form of the AgBiS2 semiconductor material, the sea urchin-shaped AgBiS2 semiconductor material and the ZnIn2S4 nanosheets with sulfur vacancies form an S-type heterojunction composite material with a cauliflower structure.
[0011] The second object of the present invention is to provide a method for preparing a sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material, comprising:
[0012] Preparation of sea urchin-shaped AgBiS2 powder: silver nitrate, bismuth nitrate pentahydrate, thiourea and ammonium acetate are mixed as raw materials, and the obtained mixed solution is reacted at 150-200°C for 4-7h; ZnIn2S4 nanosheets are in situ grown on the prepared sea urchin-shaped AgBiS2 powder to obtain a sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material.
[0013] Existing AgBiS2 semiconductor materials generally use CVD (Chemical Vapor Deposition) and CBD (Chemical Bath Deposition) to synthesize thin-film, large-grained AgBiS2 two-dimensional films, which are usually used in thin-film solar cells, photodetectors and other fields. In the present invention, a simple solvent thermal method is used to react at 150-200°C for 4-7h, and the urchin-shaped AgBiS2 formed belongs to the powder form of a three-dimensional structure, and the inventors are surprised to find that the powder form of this three-dimensional structure matches the sulfur vacancy ZnIn2S4 well in the energy band structure, and the band gap of the composite material formed is narrower than that of pure ZnIn2S4, which is conducive to the absorption of visible light. The experimental results in the embodiment also prove that the electron transfer is indeed accelerated, and its transfer path is also the most efficient S-type in the current heterojunction. In addition, the composite material is more firmly combined together, so that the specific surface area is increased, the contact area with water and pollutants is also increased, and the reaction is more sufficient; light can be reflected and absorbed multiple times on the surface of the material, thereby improving the light absorption efficiency, etc., and finally has good application prospects in many fields.
[0014] The inventors have found that the choice of reaction temperature and time can effectively regulate the nucleation rate and growth rate of the crystal nucleus. Reacting at 150-200°C for 4-7 hours will cause the ions or molecules in the system to gradually aggregate and grow at specific locations, forming "thorns" or "tentacles" of a sea urchin-like structure. If the reaction temperature is too high, the sea urchin-like morphology will collapse and cause the material to overgrow or abnormal crystal growth. When the reaction temperature is too low, the reaction rate will slow down, and the tentacles of the sea urchin-like structure may not be long enough to form a complete sea urchin-like morphology. For the formation of a sea urchin-like morphology, a certain reaction time is required to ensure the full growth and assembly of the "thorn"-like structure.
[0015] In an optional embodiment, when preparing sea urchin-shaped AgBiS2 powder, the ratio of the amounts of silver nitrate, bismuth nitrate pentahydrate, thiourea and ammonium acetate is 1:(1-1.5):(2.5-4):(1.5-4), and the concentration of metal ions in the mixed solution obtained by mixing the four is 0.1-0.2 mol / L, and the entire process of dissolving and stirring the substances is under dark conditions.
[0016] In the preparation process of sea urchin-shaped photocatalytic materials, the appropriate precursor ratio can guide the crystal to grow along a specific direction, thereby facilitating the formation of a sea urchin-shaped structure. 3+ When the amount of metal ions is relatively large, it will dominate the growth of certain crystal faces during the crystal growth process, causing the material to grow faster on these crystal faces, thus forming sea urchin-like "thorns". 3+ Excessive amounts of metal ion precursors will accelerate the nucleation process and produce more crystal nuclei. These crystal nuclei can serve as growth points in the subsequent growth process to form multiple "thorns" of the sea urchin-like structure, making the "thorns" of the sea urchin-like material denser. For sea urchin-like photocatalytic materials, the appropriate composition can optimize their crystal structure and electronic structure, thereby improving the photocatalytic performance.
[0017] The appropriate metal ion concentration can make the crystal growth rate moderate, which is conducive to the formation of a uniform sea urchin-like structure. If the metal ion concentration is too high, it will usually lead to a higher nucleation rate, which will make the crystal grow too quickly, resulting in uneven growth of the sea urchin-like "thorns" and even agglomeration; on the contrary, if the metal ion concentration is too low, the crystal growth is slow and a complete sea urchin-like structure may not be formed. The material may exist in the form of small particles or incomplete crystal nuclei.
[0018] In an optional embodiment, when preparing the sea urchin-shaped AgBiS2 powder, silver nitrate and bismuth nitrate pentahydrate are first mixed in ethylene glycol, thiourea is added, and finally ammonium acetate is added;
[0019] Preferably, after the reaction is completed, the sample is cooled to room temperature and then centrifuged, and the sample is washed alternately with deionized water and anhydrous ethanol for 3 times or more, and then dried at 60 to 90° C. for 8 to 12 hours to obtain a sea urchin-shaped AgBiS2 powder.
[0020] In an optional embodiment, the process of in-situ growing ZnIn2S4 nanosheets on AgBiS2 powder is:
[0021] Adding AgBiS2 material to a mixed solution of propylene glycol and hydrochloric acid, dispersing by ultrasonic stirring, then adding zinc chloride, indium chloride tetrahydrate and thioacetamide, and stirring by ultrasonic stirring to obtain a solid-liquid mixture;
[0022] The solid-liquid mixture is reacted at 70-90°C in an oil bath for 2-4 hours, cooled, centrifuged, washed and dried. The inventors found that if the temperature is too low, the reaction rate will be too slow, or the heterojunction formed will be of poor quality and low crystallinity; if the temperature is too high, the material will agglomerate or grow excessively, destroying the ideal morphology and structure of the composite material.
[0023] In the present invention, during the in-situ growth process, a low-temperature one-step oil bath method is used to creatively grow the ZnIn2S4 nanosheets containing sulfur vacancies in-situ on the surface of the sea urchin-shaped AgBiS2 semiconductor material. The reaction temperature of the low-temperature oil bath method is easier to control and has better uniformity, which helps to improve the efficiency of in-situ growth, so that the ZnIn2S4 nanosheets with sulfur vacancies grow more quickly and evenly on the carrier, and obtain a composite material with better crystallinity; at the same time, this one-step oil bath method is conducive to enhancing the interface interaction between the active material ZnIn2S4 and the carrier AgBiS2, forming a tighter combination, which is very critical for improving the performance stability and synergistic effect of the composite material in photocatalytic applications. And the one-step oil bath method completes multiple reaction steps at one time under oil bath conditions, simplifies the process flow, and is more convenient than some in-situ growth methods that require multi-step operations and may involve complex processing in the middle.
[0024] In an optional embodiment, the volume ratio of glycerol to hydrochloric acid is 1:(2.5-8), and the pH value of the mixed solution of glycerol and hydrochloric acid is 2-4.
[0025] The reason why the inventors selected this volume ratio range is that glycerol is a polar molecule that can be miscible with water in any proportion. And it has a high boiling point and viscosity. The higher boiling point allows the reaction system to maintain a relatively high temperature during the oil bath process, which is conducive to increasing the reaction rate and promoting the formation of a sheet structure. At the same time, the higher viscosity can slow down the diffusion rate of the reactants, making the reaction more gentle and controllable to a certain extent, which is conducive to the growth and stability of the sheet structure. If there is too much glycerol, the viscosity of the mixed solvent will increase significantly, causing the diffusion of the reactants to be seriously hindered and the reaction rate to decrease. It is difficult for the reactants to fully contact and react, which will lead to incomplete growth of the sheet photocatalytic material and affect the yield and quality of the ZnIn2S4 material. In addition, too much glycerol will cause adhesion or agglomeration between the sheet materials, destroying the regularity of the sheet structure. The size and thickness of the sheet material may also be affected and become uneven, thereby reducing the specific surface area and photocatalytic performance of the material; when the glycerol content is too low, the mixed solvent's ability to dissolve certain precursors may decrease, resulting in increased unevenness of the reaction system.
[0026] The acidic environment was chosen because the acidic conditions would promote the decomposition of thioacetamide to release the S source and react with Zn 2+ 、In 3+ The reaction combines to generate ZnIn2S4, but a pH value that is too low means that the solution is too acidic, causing the S source to be released too quickly, which will lead to a too fast rate of generating ZnIn2S4 nanosheets and poor crystallinity. Conversely, a pH value that is too high means that the solution is too acidic, causing the S source to be released too slowly, resulting in an increase in time cost. Weighing the crystallinity and time cost of the ZnIn2S4 material, the pH value is best in the range of 2 to 4.
[0027] Preferably, the mass ratio of AgBiS2 to zinc chloride in the solid-liquid mixture is (1-3):3. Since ZnIn2S4 nanosheets grow on the surface of the sea urchin-shaped AgBiS2, if the proportion of ZnIn2S4 in the composite material is too high, a shielding effect will occur, that is, too many ZnIn2S4 nanosheets block each other and block the absorption of light by AgBiS2. If the proportion of ZnIn2S4 is too low, the utilization rate of light is not high.
[0028] More preferably, the molar ratio of zinc chloride, indium chloride tetrahydrate and thioacetamide is 1:2:(4.5-16).
[0029] The sulfur source used in this patent is thioacetamide, and the mechanism of releasing sulfur source is that thioacetamide releases H2S in acidic solution, and H2S dissolves in water and decomposes S 2-, and then combines with Zn and In to generate ZnIn2S4. In this process, the S source will volatilize in the form of H2S and cause certain losses, so the amount of thioacetamide added should be slightly excessive. At the same time, the reason why thioacetamide was chosen as the S source instead of the common Na2S is that the release rate of the S source should not be too fast or too slow. Too fast will lead to too fast a rate of generating ZnIn2S4 nanosheets and poor crystallinity. On the contrary, too slow a release rate of the S source will increase the time cost, so thioacetamide, a precursor that can adjust the release rate of the S source by controlling the pH of the solution, was chosen.
[0030] In an optional embodiment, after the solid-liquid mixture reacts, the sample is washed and dried by alternately washing it with deionized water and anhydrous ethanol for 3 times or more, and drying it at 60-90° C. for 8-12 hours.
[0031] The third object of the present invention is to provide an application of the composite material described in any one of the above items or the composite material prepared by the method described in any one of the above items in photocatalytic decomposition of water to produce hydrogen and degradation of organic pollutants, wherein the organic pollutants are tetracycline hydrochloride or rhodamine B.
[0032] After experiments, it was found that the cauliflower-shaped sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material obtained by the present invention has a 14-fold improvement in the efficiency of photocatalytic hydrogen production, a 9-fold improvement in the degradation efficiency of tetracycline hydrochloride, and a 13-fold improvement in the degradation efficiency of rhodamine B.
[0033] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0034] 1. The sulfur-vacancy-rich ZnIn2S4@AgBiS2 composite material of the present invention exhibits extremely strong stability under multiple photocatalytic cycle hydrogen production and tetracycline hydrochloride degradation tests, is easy to recycle, has a high reusability, and has good commercial value.
[0035] 2. The present invention uses a low-temperature one-step oil bath method to in-situ grow ZnIn2S4 nanosheets containing sulfur vacancies on the surface of a sea urchin-shaped AgBiS2 semiconductor material to prepare a cauliflower-shaped sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction composite material with high photocatalytic performance. The internal sulfur vacancies can act as electron capture centers to inhibit the recombination of photogenerated electron-hole pairs. Under the dual synergistic catalytic action of sulfur vacancies and S-type heterojunctions, the composite sample exhibits excellent photocatalytic hydrogen production (increased by 14 times) and degradation of tetracycline hydrochloride (increased by 9 times) and rhodamine B (increased by 13 times). BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0037] Figure 1 The electron spin resonance spectrum (ESR) of the photocatalytic materials in Example 1 and Comparative Examples 1 to 3 of the present invention, wherein the horizontal axis magnetic field represents the magnetic field intensity;
[0038] Figure 2 The scanning electron microscope (SEM), transmission electron microscope (TEM), optical photograph, high-resolution transmission electron microscope (HRTEM) morphology and element distribution diagram of the photocatalytic materials in Example 1 and Comparative Examples 1, 3, 6 and 7 of the present invention, wherein (a), (b) and (c) are SEM images of the photocatalytic materials in Comparative Example 1, Example 1 and Comparative Example 3, respectively; (d), (e) and (f) are SEM images of Comparative Example 6, SEM images of Comparative Example 7 and optical photographs, respectively; (g), (hi) and (j) are TEM, HRTEM and element distribution diagram of Example 1, respectively;
[0039] Figure 3 This is an energy dispersive spectrum (EDS) of the photocatalytic material in Example 1 of the present invention, and the table in the figure shows the proportion of each element in the material;
[0040] Figure 4 The photocatalytic performance diagram and degradation mechanism diagram of the photocatalytic material in Example 1, wherein (a) and (b) are hydrogen production and tetracycline hydrochloride degradation curve diagrams of the photocatalytic material in Example 1 and Comparative Examples 1 to 6, respectively, (c), (d) and (e) are UV-visible absorption spectra of the degradation of Rhodamine B solution, cyclic hydrogen production and tetracycline hydrochloride cyclic degradation curve diagrams of the photocatalytic material in Example 1, respectively, (f) is a superoxide radical ESR diagram of the photocatalytic material in Example 1, Comparative Example 1 and Comparative Example 3, and (g) is a schematic diagram of the mechanism of photocatalytic hydrogen production and pollutant degradation by the photocatalytic material in Example 1;
[0041] Figure 5 (a) X-ray diffraction (XRD) spectrum and (b) Fourier transform infrared spectroscopy (FT-IR) spectrum of the photocatalytic material in Example 1 before and after hydrogen production. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0043] Embodiment 1:
[0044] This embodiment provides a method for preparing a cauliflower-shaped sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material, comprising the following steps:
[0045] S1. Dissolve 4 mmol of silver nitrate and 4 mmol of bismuth nitrate pentahydrate in 40-80 mL of ethylene glycol, stir in dark for 10-30 min, then add 12 mmol of thiourea, stir in dark for 2 h, and finally add 8 mmol of ammonium acetate, stir in dark for 10-30 min to obtain a mixed solution;
[0046] S2. The mixed solution was transferred to a reactor, reacted at 150-200°C for 4-7h, cooled naturally to room temperature and centrifuged, washed alternately with deionized water and anhydrous ethanol for 5 times, and dried in a vacuum oven at 60-90°C for 8-12h to obtain a sea urchin-shaped AgBiS2 black powder;
[0047] S3. In a mixed solution of 10 mL of glycerol and 40 mL of dilute hydrochloric acid at PH = 3, 42.4 mg of AgBiS2 material was added, ultrasonically stirred and dispersed for 10 min, and then 0.5 mmol of zinc chloride, 1 mmol of indium chloride tetrahydrate and 4 mmol of thioacetamide were added, and ultrasonically stirred to obtain a solid-liquid mixture;
[0048] S4. The solid-liquid mixture was transferred to a two-necked flask, and then the flask was placed in an oil bath, reacted at 70-90°C and stirred continuously for 2-4 hours, cooled naturally, and the solid sample was separated by centrifugation. The solid sample was washed alternately with deionized water and anhydrous ethanol for 5 times, and dried in a vacuum oven at 60-90°C for 8-12 hours to obtain a cauliflower-shaped sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material.
[0049] Comparative Example 1:
[0050] This comparative example provides a method for preparing a sea urchin-shaped AgBiS2 photocatalyst, which differs from Example 1 in that only steps S1 to S2 are retained, and steps S3 to S4 are omitted.
[0051] Comparative Example 2:
[0052] This comparative example provides a method for preparing an untreated ZnIn2S4 photocatalyst, which differs from Example 1 in that only steps S3 to S4 are retained, wherein no AgBiS2 material is added in step S3, and the amount of thioacetamide is changed to 2 mmol, and the remaining steps and parameters remain unchanged. The comparative example obtains a ZnIn2S4 material without sulfur vacancies.
[0053] Comparative Example 3:
[0054] This comparative example provides a method for preparing a sulfur-vacancy-rich ZnIn2S4 photocatalyst, which differs from comparative example 2 in that the amount of thioacetamide in step S4 is changed to 4 mmol, and the remaining steps and parameters remain unchanged. The comparative example obtains a ZnIn2S4 material with sulfur vacancies.
[0055] Comparative Example 4:
[0056] This comparative example provides a method for preparing a cauliflower-shaped sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material, which differs from Example 1 in that the amount of AgBiS2 in step S3 is changed to 21.2 mg, and the other steps and parameters remain unchanged.
[0057] Comparative Example 5:
[0058] This comparative example provides a method for preparing a cauliflower-shaped sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material, which differs from Example 1 in that the amount of AgBiS2 in step S3 is changed to 63.6 mg, and the remaining steps and parameters remain unchanged.
[0059] Comparative Example 6:
[0060] This comparative example provides a method for preparing a two-dimensional thin film AgBiS2 material, comprising the following steps:
[0061] S1. Dissolve 0.2 mmol of silver chloride and 0.2 mmol of bismuth chloride in 200 mL of deionized water to prepare a precursor solution, then add 20 mL of a 0.02 mol / L sodium thiosulfate pentahydrate solution, and stir in dark for 10 to 30 min to obtain a mixed solution;
[0062] S2. Hydrochloric acid is dropped into the mixed solution obtained in step S1 to make the pH of the solution = 3, and then a clean glass sheet of 2.5 cm × 2 cm is placed in the mixed solution as a deposition substrate, reacted at 80°C in a vacuum oven for 1 h, cooled naturally, and the glass sheet is taken out, washed alternately with deionized water and anhydrous ethanol for 5 times, and dried in a vacuum oven at 60-90°C for 8-12 h to obtain a two-dimensional thin film AgBiS2 material.
[0063] Comparative Example 7: This comparative example provides a method for preparing a flaky sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material. The difference between this method and Example 1 and Comparative Example 6 is that steps S1 to S2 in Example 1 are replaced by Comparative Example 6, and steps S3 to S4 in Example 1 remain unchanged.
[0064] The photocatalysts prepared in the above Example 1 and Comparative Examples 1 to 7 are respectively recorded as Sv-ZIS@ABS-2, ABS, ZIS, Sv-ZIS, Sv-ZIS@ABS-1, Sv-ZIS@ABS-3, ABS-CBD and Sv-ZIS@ABS-2-CBD, and their morphology, structure and photocatalytic performance are tested. Among them, ZIS is the abbreviation of ZnIn2S4.
[0065] Figure 1 The electron spin resonance spectrum (ESR) of the photocatalytic materials in Example 1 and Comparative Examples 1 to 3 of the present invention shows that compared with Comparative Examples 1 to 2, Example 1 and Comparative Example 3 show obvious ESR peaks, indicating that Sv-ZIS@ABS-2 and Sv-ZIS samples are rich in sulfur vacancies.
[0066] Figure 2 The present invention shows scanning electron microscope (SEM), transmission electron microscope (TEM), optical photographs, high-resolution transmission electron microscope (HRTEM) morphology images and element distribution maps of the photocatalytic materials in Example 1 and Comparative Examples 1, 3, 6 and 7, wherein (a), (b) and (c) are SEM images of the photocatalytic materials in Comparative Example 1, Example 1 and Comparative Example 3, respectively; (d), (e) and (f) are SEM images of Comparative Example 6, SEM images of Comparative Example 7 and optical photographs, respectively; (g), (hi) and (j) are TEM, HRTEM and element distribution map of Example 1, respectively. It can be seen that the ABS material of comparative example 1 exhibits a sea urchin-like morphology, the Sv-ZIS sample of comparative example 3 shows a flower-like structural morphology formed by self-assembly of extremely thin nanosheets, and the Sv-ZIS@ABS-2 sample of Example 1 shows a cauliflower-like special three-dimensional spatial structural morphology. In addition, the two-dimensional thin film AgBiS2 prepared by the conventional CBD method in comparative example 6 exhibits a flat grain morphology, and the sheet-like Sv-ZIS@ABS-2-CBD composite material formed by growing Sv-ZIS nanosheets using this two-dimensional thin film AgBiS2 as a carrier in comparative example 7 exhibits a flat nanosheet morphology. On the other hand, Figure 2 As can be seen in (h), there are two clear dividing lines at the interface between the composite sample Sv-ZIS and ABS. The area surrounded by the dividing lines belongs to the (200) crystal plane of ABS, and the area outside the dividing lines belongs to Sv-ZIS. The lattice fringes of Sv-ZIS were then enlarged to obtain the HRTEM image of the sample. Figure 2 (i) shows that the lattice spacing is 0.32nm, corresponding to the (102) crystal plane, and there are many sulfur vacancies in the lattice. In addition, the elements Ag, Bi, S, In and Zn are evenly distributed.
[0067] Figure 3 Energy dispersive spectrometer (EDS) of the photocatalytic material prepared in Example 1 of the present invention. It can be seen that the sample has typical characteristic peaks of elements such as Ag, Bi, S, In and Zn, and the atomic ratio of each element shows that sulfur vacancies do exist.
[0068] Figure 4 The photocatalytic performance diagram and degradation mechanism diagram of the photocatalytic material in Example 1, wherein (a) and (b) are hydrogen production and tetracycline hydrochloride degradation curve diagrams of the photocatalytic material in Example 1, Comparative Examples 1 to 5, and Comparative Example 7, respectively; (c), (d) and (e) are UV-visible absorption spectrum diagrams, cyclic hydrogen production and cyclic degradation curve diagrams of tetracycline hydrochloride of the degradation of Rhodamine B solution of the photocatalytic material in Example 1, respectively; (f) is a superoxide radical ESR diagram of the photocatalytic material in Example 1, Comparative Example 1 and Comparative Example 3; and (g) is a schematic diagram of the mechanism of photocatalytic hydrogen production and pollutant degradation by the photocatalytic material in Example 1.
[0069] It can be seen that compared with the ZIS material without sulfur vacancies, the Sv-ZIS sample containing sulfur vacancies showed stronger photocatalytic hydrogen production and tetracycline hydrochloride degradation performance. After introducing sulfur vacancies into the composite samples, it can be found that Sv-ZIS@ABS-1, Sv-ZIS@ABS-2, Sv-ZIS@ABS-2-CBD and Sv-ZIS@ABS-3 all showed enhanced photocatalytic performance. Under the synergistic effect of sulfur vacancies and heterojunction, the Sv-ZIS@ABS-2 photocatalytic composite material showed 4560.2μmol h -1 g -1The photocatalytic hydrogen production performance and photocatalytic tetracycline hydrochloride degradation efficiency of 94.02% are 14 times and 9 times higher than those of the untreated ZIS material without sulfur vacancies (Comparative Example 2), respectively, and the degradation of rhodamine B is almost completed within 60 minutes. The reason why the performance differences between Sv-ZIS@ABS-2 and Sv-ZIS@ABS-2-CBD with the same composite ratio are large may be that the ABS film samples prepared by the CBD method need to be grown on a certain substrate, which determines that compared with the photocatalytic material in Example 1, its contact area with water is greatly reduced, and the two-dimensional plane morphology leads to a smaller specific surface area. These factors work together to weaken the photocatalytic performance of Sv-ZIS@ABS-2-CBD. The reason why ABS does not show obvious photocatalytic performance may be that its conduction band position is higher than the reduction potential of H2, which makes the electrons at the conduction band unable to convert H + Reduced to H2. In addition, the total amount of hydrogen produced by the Sv-ZIS@ABS-2 photocatalytic composite material in each 3h cycle is very stable, and the sample still maintains a degradation efficiency of 87.56% after five cycles of degradation. After testing the superoxide free radicals, it was found (corresponding to Figure f) that the Sv-ZIS@ABS-2 photocatalytic composite material showed the strongest ESR peak, followed by the peak of the Sv-ZIS material, and the ABS sample had almost no response, so it was obtained. Figure 4 (g) Schematic diagram of the photocatalytic mechanism. The electrons are finally transferred to the conduction band of Sv-ZIS to participate in the reduction reaction, while the holes are located in the valence band of ABS to participate in the oxidation reaction. This transfer path of photogenerated carriers proves that the heterojunction inside the Sv-ZIS@ABS-2 photocatalytic composite material is an S-type heterojunction.
[0070] Figure 5 The (a) X-ray diffraction (XRD) pattern and (b) Fourier transform infrared spectroscopy (FT-IR) pattern of the photocatalytic material before and after hydrogen production in Example 1. It can be seen that after the photocatalytic cyclic hydrogen production experiment, its XRD and FT-IR patterns are almost the same as before the experiment, which indicates that the structure of the sample has not changed during this process, which means that the photocatalytic material in Example 1 has extremely strong stability and high reusability.
[0071] The above specific implementation methods further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific implementation methods of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material, characterized in that: The invention discloses an S-type heterojunction composite material formed by growing ZnIn2S4 nanosheets containing sulfur vacancies on a sea urchin-shaped AgBiS2 semiconductor material. When the ZnIn2S4 nanosheets grow on the sea urchin-shaped AgBiS2, they show a cauliflower-like morphology.
2. The sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material according to claim 1, characterized in that: The thickness of the ZnIn2S4 nanosheet containing sulfur vacancies is 15-25nm and the size is 500-800nm. When the ZnIn2S4 nanosheet grows on the sea urchin-shaped AgBiS2, it exhibits a cauliflower-like morphology, forming a nanosheet with a thickness of 15-25nm and a size of 50-100nm.
3. The sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material according to claim 1, characterized in that: The sea urchin-shaped AgBiS2 semiconductor material is micron-sized and has a cubic crystal structure.
4. The method for preparing a sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material according to any one of claims 1 to 3, characterized in that: include: Preparation of sea urchin-shaped AgBiS2 powder: silver nitrate, bismuth nitrate pentahydrate, thiourea and ammonium acetate are mixed as raw materials, and the obtained mixed solution is reacted at 150-200°C for 4-7h; ZnIn2S4 nanosheets were in situ grown on the prepared sea urchin-shaped AgBiS2 powder to obtain a sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material.
5. The method for preparing a sulfur vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material according to claim 4, characterized in that: When preparing sea urchin-shaped AgBiS2 powder, the molar ratio of silver nitrate, bismuth nitrate pentahydrate, thiourea and ammonium acetate is 1:(1-1.5):(2.5-4):(1.5-4), and the concentration of metal ions in the mixed solution obtained by mixing the four is 0.1-0.2 mol / L. The whole process of dissolving and stirring the substances is carried out in the dark.
6. A method for preparing a sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material according to claim 4, characterized in that: When preparing the sea urchin-shaped AgBiS2 powder, silver nitrate and bismuth nitrate pentahydrate are first mixed in ethylene glycol, then thiourea is added and mixed, and finally ammonium acetate is added; Preferably, after the reaction is completed, the sample is cooled to room temperature and then centrifuged, and the sample is washed alternately with deionized water and anhydrous ethanol for 3 times or more, and then dried at 60 to 90° C. for 8 to 12 hours to obtain a sea urchin-shaped AgBiS2 powder.
7. A method for preparing a sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material according to claim 4, characterized in that: The process of in-situ growth of ZnIn2S4 nanosheets on AgBiS2 powder is as follows: Adding AgBiS2 material to a mixed solution of propylene glycol and hydrochloric acid, dispersing by ultrasonic stirring, then adding zinc chloride, indium chloride tetrahydrate and thioacetamide, and stirring by ultrasonic stirring to obtain a solid-liquid mixture; The solid-liquid mixture is reacted at 70-90°C in an oil bath for 2-4 hours, cooled, centrifuged, washed and dried.
8. The method for preparing a sulfur-vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material according to claim 7, characterized in that: The volume ratio of glycerol to hydrochloric acid is 1:(2.5-8), and the pH value of the mixed solution of glycerol and hydrochloric acid is 2-4; Preferably, the mass ratio of AgBiS2 to zinc chloride in the solid-liquid mixture is (1-3):3; More preferably, the molar ratio of zinc chloride, indium chloride tetrahydrate and thioacetamide is 1:2:(4.5-16).
9. The method for preparing a sulfur vacancy-rich ZnIn2S4@AgBiS2 heterojunction photocatalytic composite material according to claim 7, characterized in that: After the solid-liquid mixture reacts, the sample is washed and dried by alternately washing it with deionized water and anhydrous ethanol for 3 times or more, and then drying it at 60 to 90° C. for 8 to 12 hours.
10. Use of the composite material according to any one of claims 1 to 3 or the composite material prepared by the method according to any one of claims 4 to 9 in photocatalytic decomposition of water to produce hydrogen and degradation of organic pollutants, wherein the organic pollutants are tetracycline hydrochloride or rhodamine B.